Strategı Pemecahan Masalah Untuk Mengatası Rendahnya Kemampuan Pemecahan Masalah Sıswa Kelas IV Sekolah Dasar - Silmi Awalyatun Nisa; Roni Wahyu Wandani (Jurnal Elementaria Edukasia, 2023)
The background for writing this study is the low problem-solving ability of elementary school students. This study aims to analyze the factors that cause low problem-solving abilities that occur in students and examine solutions that can be used for problem-solving processes in classroom learning. The method used in writing this article is through Literature Study. Literature Study is a study that collects various data and information through various sources of reading material, such as books, articles, journals, and so on. The topic of discussion in this article is to deepen the study of the solutions offered for student problem solving problems and also explain the factors causing the low problem solving of elementary school students and the IDEAL AND POLYA stages as strategic solutions that can be used in the problem solving process in mathematics lessons. With this study is expected to provide solutions to the process of solving student problems in elementary schools